Co-adaptation of Streptococcus mutans to simulated microgravity and silver nitrate - Fernander, Mizpha C.; Spurgeon, Kelyah; Graves, Jada; Guess, Wynter; Miller, Jordan; Mangum, Chanell; Graves, Joseph L.; Thomas, Misty D. (Frontiers in Astronomy and Space Sciences, 2023)
To sustain life on extended space missions, it is essential to maintain a clean potable water. NASA currently uses iodine as the primary biocide in the Potable Water Dispenser on the International Space Station and have recently proposed a potential switch to silver based antimicrobials. Streptococcus mutans is the primary etiological agent of dental caries and part of the normal oral flora. In our previous work, we examined the 100-day adaptive response of S. mutans to simulated microgravity (sMG). Here, we examined the evolutionary co-adaptation of S. mutans under sMG and silver nitrate (AgNO3) to better understand the consequences of using silver as a primary biocide in space and the impact on the evolution of microbes from the oral microbiome. To do this, we adapted 4 populations of S. mutans under sMG and co-adapted 4 populations in sMG and silver nitrate (sMGAg) using High Aspect Ratio Vessels for 100-days. Genomic analysis at multiple time points showed that S. mutans in sMG evolved variants consistent with our previous findings while also acquiring novel mutations in the glutathione reductase gorA. The co-adapted populations showed mutations specific for the environment in ciaH/R, PBP1a, trkA and trkB. We also assessed virulence phenotypes, and while sMG increased antibiotic susceptibility, sucrose dependent adhesion and in some populations, acid tolerance, co-adaptation to silver nitrate reversed this effect. Overall, this data shows that the use of silver as a biocide in sMG, has the potential to evolve strains with novel genotypic and phenotypic traits.